2012
DOI: 10.1152/ajpcell.00449.2011
|View full text |Cite
|
Sign up to set email alerts
|

Enrichment of neonatal rat cardiomyocytes in primary culture facilitates long-term maintenance of contractility in vitro

Abstract: Enrichment of neonatal rat cardiomyocytes in primary culture facilitates long-term maintenance of contractility in vitro. Am J Physiol Cell Physiol 303: C1220 -C1228, 2012. First published August 29, 2012; doi:10.1152/ajpcell.00449.2011.-Long-term culture of primary neonatal rat cardiomyocytes is limited by the loss of spontaneous contractile phenotype within weeks in culture. This may be due to loss of contractile cardiomyocytes from the culture or overgrowth of the non-cardiomyocyte population. Using the mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 40 publications
(44 reference statements)
0
19
0
Order By: Relevance
“…Another contributing factor could be that fibroblast attachment and proliferation is higher on stiffer substrates [49, 50]. Our primary neonatal rat ventricular myocyte cultures have some contamination from non-mycoyte cell populations, which could potentially attach, spread, and divide more easily on PDMS, causing delamination of cardiac myocytes over long-term culture [51]. More studies are needed to tease apart these different cues to identify which parameters are most important for improving the health and lifetime of engineered cardiac tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Another contributing factor could be that fibroblast attachment and proliferation is higher on stiffer substrates [49, 50]. Our primary neonatal rat ventricular myocyte cultures have some contamination from non-mycoyte cell populations, which could potentially attach, spread, and divide more easily on PDMS, causing delamination of cardiac myocytes over long-term culture [51]. More studies are needed to tease apart these different cues to identify which parameters are most important for improving the health and lifetime of engineered cardiac tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Using fluorescence activated cell sorting technique, Banerjee et al 37 showed that the population of cardiomyocytes in the day 1 rat heart was 62%, cardiac fibroblasts comprised 30%, and nonmyocytes and nonfibroblasts consist of 8%. After 1-3 days of culture, a nongenetic method by Nguyen et al 38 demonstrated that the population of cardiomyocytes was 25.8% and nonmyocytes was 54.2%. Thus, by adding 10 ÎŒM cytosine arabinoside, a fibroblast proliferation inhibitor, yasui et al 22 were able to fabricate a BAH with neonatal cardiac cells, which was capable of beating up to 30 days.…”
Section: Discussionmentioning
confidence: 99%
“…The primary neonatal rat cardiomyocyte culture. The primary neonatal rat cardiomyocytes (PNRCMs) were separated and purified from the ventricles of new-born 1-2-day-old SD rats, as previously described 26 . PNRCMs were cultured in 25 mM glucose DMEM (containing 10% FBS) in an incubator (5% CO 2 , 37 °C) for 72 h. The cells were identified as cardiomyocytes by immunofluorescence staining of cardiac troponin (cTnT).…”
Section: Methods Chemicals and Reagents Cvb-d (Purity >98%mentioning
confidence: 99%